Why did the Japanese Government take so long to approve the intrauterine contraceptive device?. (August 2018) - Homei, Aya
Abstract: While the majority of East Asian countries embraced the modern intrauterine device (IUD) during the 1960s, the sale and distribution of the IUD in Japan was not authorized until 1974. In this paper, I address why the Japanese Government took so long to permit the use of the IUD. Firstly, I examine scientific debates in Japan during the early 1950s on the efficacy of the IUD and associated health risks, to illustrate how the Government's conservative attitude was fostered by a co-constitutive relationship between health officials and leading obstetrician-gynaecologists who believed that the IUD was dangerous and likely to induce abortion. I also trace the Japanese Government's rapidly changing attitude through the 1960s, and analyse the influential interaction between national policy making and the enthusiastic response of a small number of Japanese doctors to the transnational movement to curb population growth in developing countries. I argue that the specific ways in which biomedical discourse was shaped by the sociopolitical position of doctors in relation to the Government's health administration explains the Japanese Government's resistance to use of the IUD. However, I also note that the Government's dramatic change in attitude was influenced directly by transnational reproductive politics. This paper will enhance the history of reproductive politics in post-war Japan, which has tended to focus on the politics surrounding abortion and the contraceptive pill.